2020
DOI: 10.7150/ijms.44041
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma accelerates the healing process of peripheral nerve crush injury in rats

Abstract: The objective of this study was to evaluate the effect of non-thermal plasma (NTP) on the healing process of peripheral nerve crush injuries, which can occur during dental implant procedures. For this, a rat model of sciatic nerve crush injury (SNCI) was adopted. The rats were divided into three groups: non-nerve damage (non-ND), nerve damage (ND), and ND+NTP group. To evaluate the sciatic nerve (SN) function, the static sciatic index was calculated, and the muscle and SN tissues were subjected to a histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Therefore, we studied the effect of NTP application after SNCI in rats by reproducing PNI in a previous study, which was the first study that used NTP in PNI. 21 A microvascular clamp was compressed for 60 s to inflict crush injury, and NTP was applied similarly as in the current study. The results showed that nerve function was completely restored in the ND þ NTP group after three weeks, whereas only 60% of the nerve function was restored in the ND group without NTP application.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we studied the effect of NTP application after SNCI in rats by reproducing PNI in a previous study, which was the first study that used NTP in PNI. 21 A microvascular clamp was compressed for 60 s to inflict crush injury, and NTP was applied similarly as in the current study. The results showed that nerve function was completely restored in the ND þ NTP group after three weeks, whereas only 60% of the nerve function was restored in the ND group without NTP application.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the result of IF staining for CD68 and type I collagen in our previous study showed significantly increased type I collagen and reduced macrophages in the muscle tissue around the sutured site. 21,22 Therefore, NTP might prevent a chronic inflammatory reaction on the damaged muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations